Spindle-cell carcinoma of larynx: a case report - Keleş, Erol; Karlıdağ, Turgut; Eroğlu, Orkun; Özercan, İbrahim Hanifi (My University, 2016)
Spindle-cell carcinoma of the larynx are extremely rare and high-grade malignancy. In this article, we report a 56-year-old male case who was admitted with a complaint of hoarseness and pathologically diagnosed with a spindle-cell carcinoma of the larynx.
Larenksin iğsi hücreli karsinomu: Olgu sunumu
Keywords: Carcinoma; Hoarseness; Humans; Laryngeal Neoplasms; Male; Middle Aged; carcinoma; case report; hoarseness; human; larynx tumor; male; middle aged; pathology